Jejak Historis Kebijakan Pendidikan Islam di Indonesia dalam Lintasan Sejarah - Bella, Sinta; Irawan, M. Ferry; Shaleh (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
Education in Indonesia has experienced various changes, in the form of policies or laws. Islamic education is an important part of indonesia’s journey to independence. Issues regarding the legality and role of religion in the national education system are then rexognized and can be applied at every level of education. This article aims to understand the history and system of Islamic education since independence, the new order and the reform era. This article is library education in Indonesia has experienced various changes, in the form of policies or laws, Islamic research where the author collects data from various references. The results of this research state the role and position of Islamic education and make the position of relegius education ( including Islamic education) an intergral part of the national education system. This law as the starting point for the revival of Islamic education within the framework of equal education policies.